The Detrimental Effect of Thyroiditis on Pregnancy Outcome of Patients Affected by Autoimmune Diseases: An Open Question - Botta, Angela; Rizzo, Francesca; Antonielli, Tatiana; Ciliberti, Alessandra; Garufi, Ester; Lanzone, Antonio; Garufi, Cristina; De Carolis, Sara (Frontiers in Pharmacology, 2022)
Few data are available evaluating obstetrical outcome when thyroiditis coexist with autoimmune diseases. Objectives of our study were: 1) To assess the prevalence of thyroiditis in pregnant women with autoimmune diseases; 2) To evaluate the effects on pregnancy outcome when different autoimmune diseases are associated with thyroiditis. Two groups of pregnant women were analysed: a study group of pregnant women with autoimmune diseases (n = 268) versus a control group of pregnant women (n = 1,150). In both groups the research for thyroid antibodies, anti-thyroid peroxidase antibodies and anti-thyroglobulin antibodies, was performed. The positivity had a prevalence of 17.54% in women with autoimmune diseases (n = 47) versus 5.57% in the control group (n = 64) (p-value < 0.00001). Only major rheumatic diseases (MRD) were analysed for pregnancy outcome (week of delivery, birth weight and birth weight percentile): systemic lupus erythematosus (SLE) n = 36, antiphospholipid syndrome (APS) n = 44 and connective tissue diseases (CTD) n = 23. MRD were divided according to positive or negative results for thyroid antibodies. Thyroiditis in CDT patients showed a detrimental effect on pregnancy outcome, in terms of earlier week of delivery: 37.86 ± 0.90 (mean ± SD) in CTD with thyroiditis versus 38.56 ± 0.73 (mean ± SD) in CTD without thyroiditis (p-value = 0.03) and lower birth weight: 2,790.71 g ± 257.17 SD in CTD with thyroiditis versus 3,019.33 g ± 305.48 g in CTD without thyroiditis (p-value < 0.05). In SLE and APS thyroiditis did not appear to influence pregnancy outcome. However, we suggest investigating anti-thyroid antibodies in all autoimmune diseases with special attention to pregnant women with thyroiditis and CTD.